Transactions on Graph Data and Knowledge - Hogan, Aidan; Horrocks, Ian; Hotho, Andreas; Kagal, Lalana (Transactions on Graph Data and Knowledge, 2023)
Transactions on Graph Data and Knowledge (TGDK) is a new journal publishing peer-reviewed research on graph-based abstractions for data and knowledge, as well as the techniques, theories, applications and results that arise in this setting. TGDK is a community-run, Diamond Open Access journal, meaning that papers are published openly on the Web without fees for authors or readers. In this preface, we provide some brief remarks about the rationale and goals of the new journal, followed by an introduction to its inaugural issue, entitled "Trends in Graph Data and Knowledge", which collects together 12 diverse vision, position and survey papers on the types of research topics that exemplify the scope of this new journal.